The round sardinella (Sardinella aurita Valenciennes, 1847) from the NW Mediterranean: a healthy and safe choice for human consumption - MUNS-PUJADAS, LAURA; CONSTENLA, MARIA; DALLARÉS, SARA; SOLER-MEMBRIVES, ANNA; PADRÓS, FRANCESC; SALA, ROSER (Mediterranean Marine Science, 2025)
The round sardinella (Sardinella aurita Valenciennes, 1847) is a common pelagic species in the NW Mediterranean, with a low economic value. To evaluate its potential as a resource, a comprehensive study including the nutritional status (proximate and fatty acid composition), zoonotic parasites and heavy metals of fish captured off the coast of Barcelona (NW Mediterranean) was carried out. Thus, 200 specimens were seasonally caught aboard commercial purse seiner fishing vessels between 2022 and 2023. Present results indicate that round sardinella should be considered a lean fish given its low total lipid content, varying seasonally, being higher in spring (1.69%) and lower in summer (0.30-0.62%). Interestingly, during summer (spawning period) and autumn, a high proportion of omega-3 long-chain polyunsaturated fatty acids (46.7-53.7% of the total fatty acids) was observed whereas palmitic acid (C16:0) (45.8% of total fatty acids) was predominant in winter. These variations, probably linked to diet composition, reproductive period and breeding strategy, are discussed. Consuming a daily meal portion of 100 g of round sardinella in summer and autumn provides 206 to 290 mg of eicosapentaenoic acid (EPA)+DHA, fitting inside the recommended levels. Similarly, the atherogenic and thrombogenic indices from this period remained within the optimal range. Moreover, the absence of zoonotic parasites and low levels of heavy metals detected indicate that its consumption, especially in autumn, is both healthy and safe for human health. Promoting this fish in autumn would also enhance sustainable fishery by distributing fishing pressure across various pelagic fish species, given the current decline in these populations.